Robotic or Open Radical Prostatectomy in Men with Previous Transurethral Resection of Prostate - Mustafa, Mahmoud; Davis, John W; Gorgel, Sacit Nuri; Pisters, Louis (Urology Journal, 2017)
Purpose: To assess and compare the surgical, oncological and functional outcomes of robotic and open radicalprostatectomy (RP) in patients with history of transurethral resection of prostate (TURP). Material and Methods: Total of 48 patients with mean ± SD age of 64.5 ± 6.0 years who had undergone TURPprior to RP were included. Thirty-one (64.58%) patients underwent robotic RP (group I) and 17 patients underwentopen RP (group II). Variables evaluated included demographic characteristics, perioperative complications, functionaland oncological outcomes. Biochemical recurrence (BCR) was defined as a detectable level of serum PSAafter RP. Continence was defined as being pad free and potency as erection with or without medication enough forpenetration. Results: All patients had undetectable PSA after RP. Four patients (12.9%) from group I and 2 patients (11.8%)from group II had positive margins (P = .9). The rates of continence were 70% and 80.81% for group I and groupII respectively (P = .47). Potency rate was 68.2% in group I and 46.1% in group II (P =. 31). The PSA value at thelast follow-up was undetectable except in 2 patients who had PSA values of 0.2 and 1ng/mL respectively. Conclusion: Robotic or open RP can be performed safely and effectively after TURP without compromising theoncological results. The outcomes of robotic RP are comparable to that of open RP. The patients who undergorobotic or open RP should be informed about increased likelihood of intra operative complications and worse postoperative functional outcomes with respect to continence and erectile function.